Mediterranean Arc, Euroregions, and Cross-Border Cooperation: Building Europe through its Borders - Durà Guimerà, Antoni; Oliveras González, Xavier (Documents d'Anàlisi Geogràfica, 2010)
Presentation of the volume 56/2.